RESPON PERTUMBUHAN DAN HASIL KUBIS BUNGA (Brassica oleracea var. botrytis,L.) PADA PEMBERIAN PGPR AKAR BAMBU DAN KOMPOSISI MEDIA TANAM - Muhamad Ikaf Husnihuda; Rahayu Sarwitri; Yulia Eko Susilowati (JURNAL VIGOR, 2017)
Research on the application of PGPR and growing media composition to plant growth cauliflower Brassica oleracea var. botrytis, L. conducted in December 2015 - February 2016 in the village of Mujahedeen - Giyanti Temanggung-. Altitude of 500 m above sea level with an average temperature of 28oC, humidity 73%, soil pH 5. latosol soil type and soil pH 5. The research was conducted using a 4 x 3 factorial experiment arranged in a Randomized Complete Block Design (RCBD) with 3 replications as blocks. The first factor PGPR (Plant Growth Promoting Rizhobakteria) bamboo root with a level 0 ml / l of water, 10 ml / l of water, 20 ml / l of water and 30 ml / l of water. The second factor is the composition of the soil media: sheep manure with a ratio of 1: 1, 2: 1 and 3: 1